Description of Nursing Students' Knowledge About the Values of Akhlakul Karimah in the Concept of Caring Behavior - Efrizal Amrullah, Akhmad; Fitriyadi, Junianto; Astutik, Emi Eliya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background : Akhlakul karimah (good morals) are all actions or behaviors that are good and commendable, indicating the perfection of a person's faith in God, whereas caring behavior is giving attention and concern. These values reflect the human side of a professional and ethical nurse in providing nursing care to clients. This study aims to determine the level of nursing students' knowledge about the values of akhlakul karimah contained in the concept of caring behavior, such as: honesty (shiddiq), justice (‘adlu), voluntariness (ihsan), wisdom (hikmah), confidence (tsiqoh), patience, humility (tawadhu), and all things that are good, where these traits can be reflected in the caring behavior of nurses. Methods : The research method used a non-experimental design with a descriptive type, a cross-sectional approach, conducted over 3 months and involved 158 respondents. Results: a total of 121 respondents (76%) had a high level of knowledge and 37 respondents (24%) had sufficient knowledge. Conclusions: In providing nursing care, the knowledge and application of akhlakul karimah contained in the concept of caring must be instilled early in students, so that when they graduate and work, they are able to reflect the character of a professional nurse. For educators, both in academics and in practice settings, they should always be figures who can provide good examples of how to apply the values of akhlakul karimah in caring behavior when working to serve clients.